2015
DOI: 10.1109/lawp.2015.2404818
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Vector Approach for Synthesis of Multi-Beam Directional Modulation Transmitters

Abstract: An orthogonal vector approach is proposed for the synthesis of multi-beam directional modulation (DM) transmitters. These systems have the capability of concurrently projecting independent data streams into different specified spatial directions while simultaneously distorting signal constellations in all other directions. Simulated bit error rate (BER) spatial distributions are presented for various multi-beam system configurations in order to illustrate representative examples of physical layer security perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 22 publications
3
75
0
Order By: Relevance
“…3 it can be observed that the standard QPSK constellation diagram, i.e., four symbols with identical amplitude and 90° phase intervals, can be detected only along the selected communication direction, 60° in this example. As it has been pointed out previously in [1] and [21] that the achievable secrecy performance is determined by the chosen PEDM, the BER simulation results presented here show the same conclusion, i.e., the smaller PEDM the narrower the BER main beams become and the greater the BER sidelobes are suppressed, as is evident in Fig. 4 under different signal to noise ratios (SNRs).…”
Section: Validation With One Legitimate Receiver In Free Spacesupporting
confidence: 85%
See 3 more Smart Citations
“…3 it can be observed that the standard QPSK constellation diagram, i.e., four symbols with identical amplitude and 90° phase intervals, can be detected only along the selected communication direction, 60° in this example. As it has been pointed out previously in [1] and [21] that the achievable secrecy performance is determined by the chosen PEDM, the BER simulation results presented here show the same conclusion, i.e., the smaller PEDM the narrower the BER main beams become and the greater the BER sidelobes are suppressed, as is evident in Fig. 4 under different signal to noise ratios (SNRs).…”
Section: Validation With One Legitimate Receiver In Free Spacesupporting
confidence: 85%
“…This approach is relatively universal as it is compatible with both static and dynamic DM systems [19], and can be readily deployed into modern digital wireless transmitters [20]. Furthermore, the orthogonal vector approach can be readily extented to endow DM transmitters with the ability for multiple independent secure beam transmissions [21]- [23] and to make the DM technology applicable in multipath environment [24], [25]. Using the orthogonal vector concept the DM synthesis can be considered as a process of injecting artificial interference that is orthogonal to the transmitted information signals along selected direction(s) in free space or at desired location(s) within a multipath environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here the limited states of the phase shifters reduce the number of independent users that can be supported in the DM systems. Further in [40,41] the orthogonal vector approach was successfully adapted for general-case multi-beam DM synthesis. By realising that the orthogonal vectors generate far-field radiation patterns, termed as interference patterns, which have nulls along all desired secure directions, the far-field pattern separation approach was developed [33].…”
Section: Multi-beam Dmmentioning
confidence: 99%